2014
DOI: 10.1089/aid.2013.0055
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the False Recent Classification Rates of Multiassay Algorithms in Estimating HIV Type 1 Subtype C Incidence

Abstract: Laboratory cross-sectional assays are useful for the estimation of HIV incidence, but are known to misclassify individuals with long-standing infection as recently infected. The false recent rate (FRR) varies widely across geographic areas; therefore, accurate estimates of HIV incidence require a locally defined FRR. We determined FRR for Botswana, where HIV-1 subtype C infection is predominant, using the BED capture enzyme immunoassay (BED), a Bio-Rad Avidity Index (BAI) assay (a modification of the Bio-Rad H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
14
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 35 publications
(44 reference statements)
2
14
0
Order By: Relevance
“…BED-CEIA can classify the types of HIV-1 infection (recent versus chronic), thus can be applied in the population-based prevalence of TDR in the recently infected individuals [Parekh et al, 2002;Jayaraman et al, 2006;Murillo et al, 2010]. Though BED-CEIA exhibits a certain rate of false-recent misclassification [Moyo et al, 2014], it still has higher predictive value of recent infection than indiscriminate sampling or sampling with younger age alone [Murillo et al, 2010]. In this study, we made further exclusion on the basis of CD4 counts and clinic diagnosis, which could be predicted to reduce false positive cases.…”
Section: Discussionmentioning
confidence: 99%
“…BED-CEIA can classify the types of HIV-1 infection (recent versus chronic), thus can be applied in the population-based prevalence of TDR in the recently infected individuals [Parekh et al, 2002;Jayaraman et al, 2006;Murillo et al, 2010]. Though BED-CEIA exhibits a certain rate of false-recent misclassification [Moyo et al, 2014], it still has higher predictive value of recent infection than indiscriminate sampling or sampling with younger age alone [Murillo et al, 2010]. In this study, we made further exclusion on the basis of CD4 counts and clinic diagnosis, which could be predicted to reduce false positive cases.…”
Section: Discussionmentioning
confidence: 99%
“…Earlier, we also reported that plasma 16S rDNA was elevated compared with healthy volunteers in a treatment-experienced HIV+ pediatric US cohort, but the values were far lower than those observed here. 24 A recent study in ART-treated, HIV-infected children in the United Kingdom 34 also found low levels of 16S rDNA in low frequency, and gut-associated bacterial species were identified by sequencing the bacterial DNA. In broad range quantitative 16S rDNA PCR assays, there is a possibility of DNA contamination, exogenous or endogenous, for which only cloning or sequencing can confirm gut bacteria.…”
Section: Discussionmentioning
confidence: 99%
“…The recentness of infection was identified in each sample using the EIA-RI (IDE/V3) assay (20,24). Recent studies have shown that a combination of assays may improve the accuracy of the data (35)(36)(37)(38). Although we did not use a multiassay algorithm, our strategy which corrects the false recentness for any patient known to be at the AIDS stage, a major factor for misclassification, was shown to be relevant at a population level (20,23,24).…”
Section: Discussionmentioning
confidence: 99%